Choice of law in relation to matrimonial property in the 21st century. (2nd January 2019) - Schuz, Rhona
Abstract : The traditional lack of consensus in relation to the choice of law rule/s governing matrimonial property has become topical and relevant over the last few years. The European Union, concerned about the impact of the disparities between the laws of Member States in this field, in the light of increasing divorce and migration, embarked on an initiative to harmonize private international law rules in relation to matrimonial property. However, the Regulation which it produced did not command universal support. Moreover, the recent demographic changes in Europe have added a new dimension to the problem. To date, relatively little attention has been paid to the choice of law implications of migration from non-Western States, in which religious or customary law governs the economic consequences of marriage and which typically have separate property systems which discriminate against women. The mass migration into Europe from such States over the past few years makes it imperative to consider the implications of the choice of law rules in relation to matrimonial property for migrants from non-Western States. Accordingly, in the light of these developments, there is a need to revisit critically the issues involved and the different approaches to choice of law in relation to matrimonial property in the light of modern choice of law theory. This article meets this need by analysing the extent to which the various approaches best promote central choice of law objectives. In addition, insights are gleaned from the experience of the Israeli legal system in relation to couples migrating from Islamic States. The conclusions drawn from this analysis, which are significantly different from those which informed the EU Regulation, will be of value to law and policymakers throughout the world, when facing the challenge of making decisions pertaining to choice of law in relation to matrimonial property in the twenty-first century.